Correlation between somatic complaints, personality traits and positivity - Petrović, Vesna; Žuljević, Dragan; Knežević, Zorica (Vojnosanitetski pregled, 2021)
Background/Aim. Many recent studies have focused on investigation the differences in personality traits and its role in promoting health and in moderating vulnerability to adversities and illness. The aim of our study was to investigate the role of somatic complaints in moderating the relationship between personality traits operationalized in Cybernetic Battery of Conative Tests (KON-6) model and positivity. Methods. The sample consisted of 512 students, 23.83 years old in average, 56.3% were female, 23% reported the presence of somatic complaints. In investigation, the Positivity Scale measuring positivity and the KON-6 measuring the activity of 6 dynamic personality traits – activity regulation system (ε), organic function regulation system (χ), defense reactions regulation system (α), attack regulation system (σ), homeostatic system coordination(δ) and regulation system integration (η) were used. Results. All of the conative personality traits were significantly correlated with positivity, except for σ. The subsample with somatic complaints reported higher scores in α and η traits, suggesting higher levels of anxiety and social reality impairment. The personality traits together with presence of somatic complaints significantly explained 26% of positivity variance, positively predicting positivity with higher activity of ε, and negatively with higher activity of α and δ. The moderating role of somatic complaints was found in two specific relations. Positivity can be predicted in a reverse manner by homeostatic system coordination (δ) but only in students with low somatic complaints, which was also the case for organic function regulation system (χ) but only in the presence of high somatic complaints. Conclusion. The positivity represents a good organizational and regulation disposition for regulating the cognitive, dynamic and motoric functions. It is also partially moderated by presence of somatic complaints. Practical benefit of these findings represents a concrete support for developing positivity in people, in order to empower people’s health.
Keywords: personality; somatoform disorders; optimism; surveys and questionnaires